Assessment of Dietary Intake, Nutrients, and Anthropometric Indices in Postmenopausal Women with Hypertension - Zahra Dashti; tahere Ramezani; Siamak Mohebi; Azadeh Kohandani; Mohammad Hozoori (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2017)
Background and Objectives: Dietary intake and anthropometric indices have a significant role in the development and progression of hypertension. In this study, anthropometric indices and effective nutrients were assessed in the development and exacerbation of hypertension in postmenopausal women with a history of hypertension.